Leading in the digital age: unlocking creative process engagement and maximizing agility performance - Yildirim, Edanur; Erdil, Oya; Tatar, Berivan (Emerald Group Publishing Ltd, 2025)
PurposeTechnological developments in recent years require businesses to update existing processes within the digitalization framework and make intensive efforts to adapt employees to these new technologies. The emergence of digital technologies has brought with it the need for a new understanding of leadership to meet the demands of the digital age. However, research examining the changes caused by digitalization in leadership understanding has been limited in management literature. Therefore, this study aims to examine digital leadership's impact on employees' agility performance, focusing on the mediating role of creative process engagement.Design/methodology/approachData were collected from 307 employees in different sectors and analyzed using structural equation modeling and the PROCESS macro for SPSS.FindingsThe results showed that (1) digital leadership is positively associated with agility performance, (2) creative process engagement positively relates to agility performance and (3) creative process engagement mediates the link between digital leadership and agility performance.Originality/valueThis study has contributed to the literature by broadening the comprehension of the link between digital leadership, creative processes engagement and agility performance.
Keywords: Leadership; Digital leadership; Creativity; Creative process engagement; Agility performance